Pañch Mahāyajñas : पञ्चमहायज्ञाः - Gupta, Vipulesh (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The Pañch Mahāyajñas occupy a foundational position in the Indian Dharmashastric tradition as the core duties of the Gṛhastha āśrama (householder stage of life). These five yajñas namely Brahmayajña, Devayajña, Pitṛyajña, Bhūtayajña, and Manuṣyayajña are not only integral to the Vedic tradition but also present a comprehensive framework of social, ethical, environmental, and intellectual responsibilities. The present research paper critically examines the concept, nature, purpose, and philosophical background of the Pañch Mahāyajñas based on authoritative verses from the Taittirīya Āraṇyaka, Manusmṛti, and Yājñavalkya Smṛti. The study concludes that the Pañch Mahāyajñas are firmly established as a moral code of Indian civilization, emphasizing balanced individual and social life. Abstract in Sanskrit Language: पञ्चमहायज्ञाः भारतीयधर्मशास्त्रीयपरम्परायां गृहस्थाश्रमस्य मूलाधाररूपेण प्रतिष्ठितास्सन्ति। एते पञ्च यज्ञाः - ब्रह्मयज्ञः, देवयज्ञः, पितृयज्ञः, भूतयज्ञः तथा मनुष्ययज्ञः न केवलं वैदिकपरम्परायाः अन्तर्गताः, अपि तु सामाजिक- नैतिक- पर्यावरणीय- बौद्धिकदायित्वानां समग्रव्यवस्थां प्रस्तौति। प्रस्तुतशोधपत्रे तैत्तिरीयारण्यम्, मनुस्मृतिः तथा याज्ञवल्क्यस्मृतिः इत्येषां प्रामाणिकश्लोकाधारेण पञ्चमहायज्ञानां संकल्पना, स्वरूपं, प्रयोजनं तथा दार्शनिकपृष्ठभूमिः सम्यग्विश्लेषिता। अध्ययनस्य निष्कर्षतः एतत् सिद्धं भवति यत् पञ्चमहायज्ञाः भारतीयसभ्यतायाः नैतिकसंहितारूपेण सुदृढतया प्रतिष्ठिताः सन्ति। Keywords: पञ्चमहायज्ञाः, धर्मशास्त्रम्, मनुस्मृतिः, याज्ञवल्क्यस्मृतिः, गृहस्थधर्मः